Studi Perkuatan Lereng Menggunakan Bronjong pada Sungai Batang Tabir Kabupaten Tebo - Pebriadi, M; Azanna, Dwitya Okky; Suhendra, Suhendra; Fadlan, Fadlan (Universitas Batanghari Jambi, 2025)
The gabion embankment project is needed to reduce erosion from river flows on roads and settlements in Embacang Gedang village. This embankment has a height of up to 8.5 m. The main material for the embankment uses 2 x 1 x 0.5 m galvanized wire gabions. Based on this data, a slope reinforcement design analysis was planned to obtain a Safety Factor value using manual calculations and Plaxis software. Soil data shows that the soil at the base of the embankment and embankment is soft clay. Modeling was carried out using plaxis 2D V8.6 software (slope stability manual before and after strengthening). The results of the analysis show that based on the results of calculating the existing safety factor with a loading of 22kN/m2, a value of 1.0734 was obtained and the manual calculation using the Fellenius method was 1.05. This value indicates that the slope condition is unsafe because it is <1.5. Calculation of the safety factor value analysis for slope conditions that have been reinforced with gabions, obtained a safety factor value of 1.6336 and a manual calculation using the Fellenius method of 2.25. This value indicates that the condition of the slope is safe and stable because the safety factor value is > 1.5. It can be concluded that the use of gabion reinforcement is quite effective in supporting the soil's bearing capacity against the load of the structure above it.